2017
DOI: 10.1038/s41598-017-14522-6
|View full text |Cite
|
Sign up to set email alerts
|

New reverse genetics and transfection methods to rescue arboviruses in mosquito cells

Abstract: Reverse genetics is a critical tool to decrypt the biological properties of arboviruses. However, whilst reverse genetics methods have been usually applied to vertebrate cells, their use in insect cells remains uncommon due to the conjunction of laborious molecular biology techniques and of specific difficulties surrounding the transfection of such cells. To leverage reverse genetics studies in both vertebrate and mosquito cells, we designed an improved DNA transfection protocol for insect cells and then demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…To recover ZIKV variants we used infectious subgenomic amplicons (ISA) (31-33) as previously described (32). For the WT ZIKV variant, three pUC57 plasmids [EVAg 001N-01891] containing overlapping regions (PF-I: 1-3428 nt, PF-II: 3354-7621 nt, PF-III: 7553-10807; all nucleotide (nt) positions based on complete viral strain sequence) covering the full ZIKV H/PF/2013 genome were used (31).…”
Section: Recovery Of Cpg-recoded Zikv Variantsmentioning
confidence: 99%
“…To recover ZIKV variants we used infectious subgenomic amplicons (ISA) (31-33) as previously described (32). For the WT ZIKV variant, three pUC57 plasmids [EVAg 001N-01891] containing overlapping regions (PF-I: 1-3428 nt, PF-II: 3354-7621 nt, PF-III: 7553-10807; all nucleotide (nt) positions based on complete viral strain sequence) covering the full ZIKV H/PF/2013 genome were used (31).…”
Section: Recovery Of Cpg-recoded Zikv Variantsmentioning
confidence: 99%
“…The ISA reverse genetics method had been used in the past for a variety of viruses with a positivestranded RNA genome such as aviviruses, alphaviruses or enteroviruses [14][15][16][17][18] . The method was proven to be extremely simple, rapid and easy to implement, but all previous results were obtained with "short" genomes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious consequence of this mechanism of action is that the probability for an individual cell to receive simultaneously upon transfection all subgenomic fragments decreases when the number of fragments increases. We previously showed that for some small (+) ssRNA viruses such as enteroviruses, the number of fragments used can be balanced by increasing in parallel the total amount of DNA to be transfected 15 . However, in the case of coronaviruses, given the length of the genome, this requirement had to be met with amounts of DNA that do not jeopardize cell biological functions, growth, and subsequent replication of the virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the efficacy of RCA for viral rescue, we chose three cell lines for transfection: Vero, HEK293T, and BHK21 Clone 13 cells (BHK21). We selected these cell lines due to their widespread use in virus rescue [23,24]. We used a CMV-driven Mayaro virus infectious cDNA clone as both the template for our RCA reactions and as our plasmid control for the transfections (Fig.…”
Section: Peak Virus Yields Are Similar For Rca-and Plasmid-derived VImentioning
confidence: 99%